Role Conflict between Land Allocation and Municipal Functions in Addis Ababa - Stebek, EN (Mizan law review, 2014)
The current accelerated growth of Addis Ababa has caused tension between the favourable aspects of urban redevelopment, and the corresponding wake-up calls against the risks of transforming various parts of the city into haphazard ‘concrete jungle’. I argue that there is role conflict in municipality authorities that are entrusted with the power to lease out urban land, and at the same time carry out the regulatory function of revising and implementing urban master plans and providing municipal services. It is argued that the land provision function of municipalities (and their corresponding interest in enhancing revenue from lease) induces them to lease out urban land to the detriment of green areas, neighborhood play fields, public parks, open spaces, riverbanks, street alignments and adequate space for bus and taxi terminals (menaheria). Such role conflict not only enhances administrative discretion and corruption, but also weakens urban land holding security, represses municipal services and adversely affects the propriety and effectiveness of urban plans.